They are all like-terms so you can add 7y+3y which equals 10y. Then subtract 10y-17y and you get a negative number; -7y
Answer:
excuses me I don't have point to ask questions so I write a thing instead of answering ❤
Answer:
You forgot to add a picture and/or more context.
Step-by-step explanation:
1.) f(x)=7(b)^x-2
x=0→f(0)=7(b)^0-2=7(1)-2=7-2→f(0)=5→(x,f(x))=(0,5) Ok
2.) f(x)=-3(b)^x-5
x=0→f(0)=-3(b)^0-5=-3(1)-5=-3-5→f(0)=-8→(x,f(x))=(0,-8) No
3.) f(x)=5(b)^x-1
x=0→f(0)=5(b)^0-1=5(1)-1=5-1→f(0)=4→(x,f(x))=(0,4) No
4.) f(x)=-5(b)^x+10
x=0→f(0)=-5(b)^0+10=-5(1)+10=-5+10→f(0)=5→(x,f(x))=(0,5) Ok
5.) f(x)=2(b)^x+5
x=0→f(0)=2(b)^0+5=2(1)+5=2+5→f(0)=7→(x,f(x))=(0,7) No
Answers:
First option: f(x)=7(b)^x-2
Fourth option: f(x)=-5(b)^x+10
Hey there!
Let's break this expression into two parts:
6(3x-1) and -10x
To solve the first part, we need to use the distributive property which states:
a(b+c) = ab+ac
Applying that to this problem, we have:
6(3x) + 6(-1) =
18x - 6
Now, we can take that -10x and put it right back in:
18x - 6 - 10x
Combine like terms and subtract the 10x from the 18x to get:
8x - 6
Hope this helps!